2021
DOI: 10.1007/s00520-021-06270-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term improvement of quality of life in patients with breast cancer: supporting patient-physician communication by an electronic tool for inpatient and outpatient care

Abstract: Purpose The effectiveness of a pathway with quality of life (QoL) diagnosis and therapy has been already demonstrated in an earlier randomized trial (RCT) in patients with breast cancer. We refined the pathway by developing and evaluating an electronic tool for QoL assessment in routine inpatient and outpatient care. Methods In a single-arm study, patients with breast cancer with surgical treatment in two German hospitals were enrolled. QoL (EORTC QLQ-C30,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…With regard to the effectiveness of patients conducting a dialogue with physicians and nurses about the ePRO profiles elicited through these apps, although this matter is beyond the scope of the intervention of our online support program and this study protocol, it has been reported that a physician's communication style with patients holds the key to the benefit of assessing HR-QOL using an electronic tool when patients initiate discussions with the physician about their HR-QOL profile [ 37 ]. Future studies will be needed to identify what approaches patients need to take to make most efficient use of their own ePRO profiles.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the effectiveness of patients conducting a dialogue with physicians and nurses about the ePRO profiles elicited through these apps, although this matter is beyond the scope of the intervention of our online support program and this study protocol, it has been reported that a physician's communication style with patients holds the key to the benefit of assessing HR-QOL using an electronic tool when patients initiate discussions with the physician about their HR-QOL profile [ 37 ]. Future studies will be needed to identify what approaches patients need to take to make most efficient use of their own ePRO profiles.…”
Section: Discussionmentioning
confidence: 99%
“…After screening the title and abstract of 6183 papers (excluding duplicates) for relevance to the subject, 131 papers were selected. A total of 67 articles [ 1 , 7 , 12 , 13 , 14 , 15 , 16 , 17 , 21 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , …”
Section: Methodsmentioning
confidence: 99%
“…For example, identifying patient’s unmet needs for the improvement of person-centered care [ 7 ], identifying the causes of problems in the patient engagement process [ 12 ], visualizing future services by presenting scenarios and prototypes through workshops [ 13 ], or offering strategies by performing persona-scenario sessions [ 14 ] could be explained as divergent processes. However, identifying the preferences of patients or clinicians for specific factors [ 1 ], analyzing barriers to a particular topic [ 15 ], assessing the usefulness of a questionnaire [ 16 ], or refining a tool and evaluating the tool’s feasibility [ 17 ] correspond to a convergence process.…”
Section: Introductionmentioning
confidence: 99%